2006
DOI: 10.1093/jn/136.3.656
|View full text |Cite
|
Sign up to set email alerts
|

An Infant and Child Feeding Index Is Associated with the Nutritional Status of 6- to 23-Month-Old Children in Rural Burkina Faso

Abstract: The measurement of child feeding practices is complex and the relation between the quality of feeding and children's nutritional status is difficult to establish. We examined this relation in rural Burkina Faso, West Africa, using an adapted version of the Infant and Child Feeding Index (ICFI). A cross-sectional study was conducted on a random sample of children (n = 2466) aged 6-35 mo in 2002. Feeding practices were assessed through a qualitative 24-h recall. ICFIs were made age specific for children aged 6-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
129
8
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(157 citation statements)
references
References 13 publications
12
129
8
8
Order By: Relevance
“…Dietary diversity indicators consistently show positive relationships with child LAZ in many contexts (40)(41)(42) . Similar to findings from other studies (18,43,44) , the number of meals and snacks consumed in the previous day was also positively associated with child LAZ. Women in northern Potosí bear numerous responsibilities both in the home and on the farm that limit the amount of time they can dedicate to child feeding (13) .…”
Section: Associations Of Infant and Child Feeding Index With Child Ansupporting
confidence: 89%
“…Dietary diversity indicators consistently show positive relationships with child LAZ in many contexts (40)(41)(42) . Similar to findings from other studies (18,43,44) , the number of meals and snacks consumed in the previous day was also positively associated with child LAZ. Women in northern Potosí bear numerous responsibilities both in the home and on the farm that limit the amount of time they can dedicate to child feeding (13) .…”
Section: Associations Of Infant and Child Feeding Index With Child Ansupporting
confidence: 89%
“…Using Demographic and Health Survey (DHS) data from these regions, chronic undernutrition was found to be significantly associated with dietary diversity (37) . Significant and positive associations between dietary diversity and nutritional status among young children have also been found in smaller-scale studies in rural Bangladesh (38) , rural Burkina Faso (12) , Kenya (39) , Mexico (40) and Mali (41) , and in a review in Africa (35) .…”
mentioning
confidence: 67%
“…Our findings suggested adequate dietary diversity to be the indicator most strongly associated with better nutrition outcomes during this period. Other studies that have used a variety of indicators aimed at capturing food variety or dietary diversity have come to similar conclusions about the importance of the diversity of young children's diets (10,12,35,37,(39)(40)(41) . Building on these previous studies, and using nationally representative data, our analysis also showed a clear association between dietary diversity and , did not achieve MDD; , achieved MDD) among children aged 6-23 months, 2007 Bangladesh Demographic and Health Survey.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In Ethiopia (Arimond and Ruel, 2002), the results were identical for the rural context only. In Burkina Faso (Sawadogo et al, 2006), there was a relationship between a slightly modified ICFI and HAZ of 6-to 36-month-old children, but in Senegal (Ntab et al, 2005) no association was found with either HAZ or linear growth velocity of 12-to 42-month-old children.…”
Section: Introductionmentioning
confidence: 81%